Creation and use of telegram-bots for learning English - Vereshchaga, Y. V. (My University, 2021)
In contemporary digital world, convenience and speed are the most important criteria when using any product. In any aspect of our life, we value these two properties even more than the cost and quality of any product or service. The same can be applied to foreign languages. Since the easier and more convenient it is to learn a particular language, the more likely it is that you will reach greater heights in this matter. Telegram bots provide us with such an opportunity, realizing a wide range of prospects in this area.
Keywords: foreign languages; Telegram bots; Internet; learning English